Method for systematic targeted isolation of homologous cDNA fragments in a multiplex format. (May 2004) - Ohara, Reiko; Koga, Hisashi; Kikuno, Reiko; Ohara, Osamu
In this study, a two-step method for systematic multiplex cloning of homologous cDNAs from related species was developed. The first step, called MUCH (multiplex cloning of homologous genes), is cloning of partial but authentic cDNA fragments of homologous cDNAs by hybridization to arrayed cRNA probes of specified genes on a nylon membrane, followed by PCR amplification of the hybridized fragments. The second step is PCR-based screening of a library that contains longer cDNA inserts based on the sequences obtained in the first step. To evaluate this method, we tried to isolate mouse counterparts of 53 human large cDNAs by MUCH and could successfully isolate 32 mouse counterpart cDNAs from a single library. Complete sequencing of two mouse cDNAs isolated by PCR-based screening further demonstrated that this method enabled us to isolate multiple homologous cDNAs in parallel. We thus expect that this method could be applied to high-throughput cloning of homologous cDNAs in related species.